2013
DOI: 10.3109/14659891.2013.765515
|View full text |Cite
|
Sign up to set email alerts
|

The association of tobacco use and gender to cardiac rehabilitation outcomes: a preliminary investigation

Abstract: Introduction Cardiac rehabilitation (CR) outcomes are measured in terms of cardiovascular disease (CVD) risk factor reductions, and these predict long-term cardiac status. This report examines whether reported tobacco use has differential effects on successful cardiovascular risk factor modification, especially for women who have greater smoking-related CVD consequences than men. Methods A retrospective cohort analysis was conducted on 1138 adults (74% male) with diagnosed CVD who participated in ≥7 weeks of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…This lack of gains could be a result of a variety of factors, for example, smokers spend fewer minutes exercising per session in CR than non-smokers (Digenio et al, 1992). Regardless of the proximal cause, current smokers are less likely to reach maximal capacity exercise goals at the end of CR (Weinberger et al, 2014) and current smoking is associated with less gain in health-related quality of life (Oldridge et al, 1998). There is also compelling evidence that smoking directly inhibits fitness gains.…”
Section: Discussionmentioning
confidence: 99%
“…This lack of gains could be a result of a variety of factors, for example, smokers spend fewer minutes exercising per session in CR than non-smokers (Digenio et al, 1992). Regardless of the proximal cause, current smokers are less likely to reach maximal capacity exercise goals at the end of CR (Weinberger et al, 2014) and current smoking is associated with less gain in health-related quality of life (Oldridge et al, 1998). There is also compelling evidence that smoking directly inhibits fitness gains.…”
Section: Discussionmentioning
confidence: 99%
“…Adherence to the training sessions was higher in men (47%) than in women (40%) 11 t-test Wahlstrom 2023 [ 80 ] Patients with AF n = 64 (28 men, 36 women) Yoga 12 Weeks CR completion: 100% 11 t-test Warner 1995 [ 88 ] Patients were referred after MI, CABG, percutaneous balloon angioplasty, cardiomyopathy, and/or stable angina n = 719 (553 men 166 women) Aerobic 260 Weeks CR completion: 12% 69/553 men, 8% 14/166 women. Adherence was 70% for men and 68% for women 12 t-test and ANCOVA Weinberger 2014 [ 86 ] Patients with PTCA, CABG, MI, valve replacement, CAD, CHF, angina or cardiomyopathy n = 1138 (843 men, 295 women) Not described ≥ 7weeks; average 11 weeks CR completion: 49% Adherence was 11.5 weeks for men and 11.4 weeks for women 12 Other (Logistic regression) Willenheimer 1998 [ 38 ] Patients with HF and ejection fraction < 45% n = 33 (27 men, 6 women) Aerobic 16 Weeks CR completion: 91% Adherence for men was 78% and for 67% women 12 t-test Wise 2012 [ 51 ] Patients with CHF (NYHA level I-III) also diagnosed with CAD, cardiomyopathy, valvular disease, and or/tachycardia n = 232 (172 men, 60 women) Aerobic and Strength 12 Weeks + median of 4 extra weeks CR completion: 100% All patients attended at least 40% of sessions. …”
Section: Resultsmentioning
confidence: 99%
“…Weinberger et al concluded that HDL cholesterol levels improved more in men compared to women after CR [ 86 ]. However, the type of exercise prescribed during CR intervention was not specified in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, those who smoke seem to be less likely to enroll to CR and more likely to drop out if they enroll, which could be due to less financial resources and limited education (115). The benefits of smoking cessation may not be as obvious to smokers because of a variety of reasons: for example, smokers show less measurable improvements (e.g., heart rate response) with regard to physical exercise (117) and have a lower likelihood of reaching their fitness goals if they complete CR (118). It is thus suggested that smokers are provided with more attention, information, and additional support, by trying several approaches such as medication or smoking cessation programs (115).…”
Section: Discussionmentioning
confidence: 99%